Current Use of Platelet Rich Fibrin in Sinus Floor Augmentation: a Literature Review - Jennifer Tjokro; Mappangara S (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Implant placement in posterior maxilla alveolar ridge might be challenging due to progressive ridge resorpsion and poor bone quality caused by intrasinus positive pressure, vascular interruption to bone plate, and absence of occlusal loads. Many attempts were made to develop convenient and predictable bone augmentation techniques in the area. Maxillary sinus floor elevation is the most predictable and frequently used method nowadays. The use of platelet-rich fibrin (PRF), which is an autologenous biomaterial, has various advantages in sinus floor augmentation. This article has purpose in review the literature on the current possibilities of PRF usage in sinus floor augmentation. Literature review: Maxillary sinus floor augmentation is done by lifting the Schneiderian membrane and inducing bone formation in the created space. There are two types of approaches; lateral and trans-alveolar approach. Schneiderian membrane perforation may cause complications in the augmentation procedure. PRF is made of fibrin matrix, containing high concentrations of platelets, growth factors, fibrin, and leukocytes, which promotes wound healing and natural bone regeneration. PRF can be used as a sole filling material, as an addition to graft materials, as a membrane to seal bone graft in lateral sinus augmentation approach, to protect sinus membrane, and to aid healing in membrane perforation. PRF acts as an optimized blood clot, providing stability and releasing growth factors in promoting bone formation. Conclusion: Within the limitations of this review, it is shown that PRF provides a safe, reliable, and easy method as a filling material, protective membrane, and in managing ruptured membrane.